Laila Porras, L’évolution des inégalités de revenus et de la pauvreté dans la transformation post-socialiste. Une analyse institutionnelle des cas tchèque, hongrois et russe - Laila Porras (Revue de la Régulation)
The post-socialist transformation has had definite effects on income inequality and distribution in all former socialist countries. This thesis analyzes the determinants of trends related to income inequality and poverty in three countries: Czech Republic, Hungary and Russia during the period 1989-2005. The study takes into account four factors to explain the different national paths of transformation: historical specificity and socialist heritage, initial conditions and transformation strategy, policies and institutions related to the labor market and, eventually, the role of the State in income redistribution. We have referred to economic theories dealing with institutional evolution and systemic change.